Cultures of Care in Irish Medical History, 1750-1970
XII, 258 p.
Keywords: Exploring aspects of Irish medical history, from the nature and proposed remedies for various illnesses in eighteenth century Ireland, to the treatment of influenza in twentieth-century Ireland, this book shows how the cultures of medical care evolved over three centuries.